Is Indian Education System Ready for Digital Transformation - Sharma, Anup; Gajera, Jenith; Rajkumar; Omkar; Pawan, (International Journal of Scientific Research and Management (IJSRM), 2021)
The novel coronavirus has changed the entire perspective of education for the world. To follow the rule of social distancing and to prevent getting gathered at one place in a large number of people the educational institutions from all over the world have given holidays. Initially, no one knew that this time the pandemic would have longterm effects and hence all the educational institutions have begun their curriculum through online mode. As this is a huge step towards technology and this cannot happen overnight the educational institutions are using the already available sources for example Google meet, zoom meeting, Google classroom, etc. while some of the institutions who are advanced in technology have created their applications and websites for their curriculum. And taking advantage of this situation now the software companies are offering schools, colleges their support for creating online portals for education. Online education can be effective in digitally advanced countries because they would have all the necessary tools for the purpose while the other countries will suffer in this area. Due to this number of problems were encountered. Where there are several negative impacts on the education sector throughout the world there is also a very big positive impact that the entire educational sector is becoming digital. The process which would have taken a decade to be formed is happening in just a small time only due to this crisis. The next year might not be the best for the education sector and that is an undeniable fact but the rest of the upcoming years after that will be the future and a lot of advantages would come from that. From the student's perspective right now they are facing issues with almost everything in their schools/colleges although the staff is trying their best to tackle the situation there is a lack of resources and tools to do so. In these crucial times, the government has stepped forward and will help in the formation of the new educational system where everything will be digitized and fulfill the needs of the traditional system adding more benefit to the same.